2011
DOI: 10.1007/s10557-011-6302-z
|View full text |Cite
|
Sign up to set email alerts
|

Heart Protection by Combination Therapy with Esmolol and Milrinone at Late-Ischemia and Early Reperfusion

Abstract: IntroductionThe present study determined whether late-ischemia/early reperfusion therapy with the β1-adrenergic receptor (AR) blocker esmolol and phosphodiesterase III inhibitor milrinone reduced left ventricular (LV) myocardial infarct size (IS).Methods and ResultsIn an ischemia/reperfusion rat model (30-min ischemia/4-hr reperfusion), esmolol, milrinone or esmolol + milrinone were intravenous (IV) infused over 10 min (from the last 5min of ischemia to the first 5min of reperfusion). LV-IS were 48.9 ± 8.9%, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Previous studies showed that milrinone administration stimulated immediate accumulation of cAMP and elevation of PKA in the liver tissue, and pretreatment with a PKA inhibitor prevented milrinone-induced PreC [14,15]. In heart, milrinone-induced PostC also increased myocardial PKA activity and Akt phosphorylation, and reduced myocardial infarct size and myocyte apoptosis [16]. Thus, it is possible that milrinone-induced hepatic PostC is associated with the activation of PKA and the PI3K/Akt-dependent pathway.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies showed that milrinone administration stimulated immediate accumulation of cAMP and elevation of PKA in the liver tissue, and pretreatment with a PKA inhibitor prevented milrinone-induced PreC [14,15]. In heart, milrinone-induced PostC also increased myocardial PKA activity and Akt phosphorylation, and reduced myocardial infarct size and myocyte apoptosis [16]. Thus, it is possible that milrinone-induced hepatic PostC is associated with the activation of PKA and the PI3K/Akt-dependent pathway.…”
Section: Discussionmentioning
confidence: 93%
“…Second, we did not measure systemic hemodynamics such as blood pressure and heart rate in this study. It has been shown that milrinone treatment (50 µg/kg) before liver ischemia [15], or after myocardial ischemia [16] did not affect systemic hemodynamics. In another study, wortmannin or L-NAME administered 5 min before reperfusion also did not affect systemic hemodynamics in myocardial infarction models [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of differences in cAMP-independent actions and compartimentation of cAMPmediated signaling [49], the combined application of milrinone and metoprolol may bear potential benefits on myocardial function [8,14,49,55]. To date, combination therapy of ßblocker and phosphodiesterase inhibitor has been used either as a bridge to ß-blocker therapy in patients with severe heart failure or as a twitch instead of dobutamine for the cardiac patient dependent on inotropic support and started on ß-blocker therapy [56].In the latter patients, chronic ß-adrenergic stress causes adrenergic desensitization thereby blunting the inotropic response in particular to dobutamine but also to milrinone [57].…”
Section: Resultsmentioning
confidence: 99%
“…Group II received a bolus intravenous tail vein injection of milrinone (50 mg/kg in 250 mL) slowly over 10 minutes. 14,15 Finally, group III received an intravenous tail vein injection of milrinone prepared in PLGA-MPs in an equivalent dose and volume as in group II. The reason for using empty MPs as a control was to ensure that these particles per se had no effect on cardiac function or other inadvertent toxicity.…”
Section: Ligation Of Left Anterior Descending Coronary Artery and Intmentioning
confidence: 99%